1984
DOI: 10.2307/1129996
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: Parent-Child Play Interaction and Peer Interactive Competence

Abstract: A multimeasure, multicontext study of the relationship between father-child and mother-child play and children's competence with preschool peers was conducted. 13 boys and 14 girls, ages 3-4 years, and their parents participated. Children were videotaped while playing with each parent separately for 20 min in their homes. Children's social competence with their peers was independently evaluated by 3 measures: (1) rankings of preschool teachers of popularity with peers, (2) Q-sort ratings of children's competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
213
2
10

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(246 citation statements)
references
References 15 publications
21
213
2
10
Order By: Relevance
“…First, the hypothesis tested is based on an assumption of socialization theory that father-child play affects the child's psychosocial development [MacDonald and Parke, 1984]. While the results reported here are consistent with this assumption, they are based on correlations and alternative accounts of the correlations are certainly possible.…”
Section: Limitations and Future Directionssupporting
confidence: 50%
See 2 more Smart Citations
“…First, the hypothesis tested is based on an assumption of socialization theory that father-child play affects the child's psychosocial development [MacDonald and Parke, 1984]. While the results reported here are consistent with this assumption, they are based on correlations and alternative accounts of the correlations are certainly possible.…”
Section: Limitations and Future Directionssupporting
confidence: 50%
“…It is well known that parent-child physical play is an important component of human socialization [Barth and Parke, 1993;Lindsey et al, 1997;MacDonald, 1993;MacDonald and Parke, 1984;Parke et al, 1988]. Sex differences appear to be the rule in this domain: boys engage in more RTP than their female counterparts in all cultures investigated to date [Pellegrini and Smith, 1998].…”
Section: Play and Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Social learning theory suggests that children learn particular behaviours in relationships with their parents and siblings and that these behaviours generalise to their interactions with peers and friends 68,69 . Attachment theory proposes that children's relationships with peers and siblings are influenced by internal working models of relationships which are carried forward from their earliest relationships with attachment figures 70,71 .…”
Section: Sibling Bullying -Is There a Link To Peer Bullying?mentioning
confidence: 99%
“…Social learning theorists have suggested that children learn particular behaviors in relationships with their parents and siblings, and that these behaviors then generalize to their interactions with peers and friends (37,38) . Attachment theory proposes that children ' s relationships with peers and siblings are infl uenced by internal working models of relationships which are carried forward from their earliest relationships with attachment fi gures (39,40) .…”
Section: Bullied At Home/bullied At School ?mentioning
confidence: 99%